Cross-border banking and the international transmission of financial distress during the crisis of 2007-2008 - Alexander Popov; Gregory F. Udell (European Central Bank (ECB), 2010)
We study the effect of financial distress in foreign parent banks on local SME financing in 14 central and eastern European countries during the early stages of the 2007-2008 financial crisis. We use survey data on applicant and non-applicant firms that enable us to disentangle effects driven by shocks to the banking system from recession-driven demand shocks that may vary across lenders. We find strong evidence that credit tightened in the relatively early stages of the crises caused by the following types of bank financial distress: 1) low equity ratio; 2) low Tier 1 capital ratio; and 3) losses on financial assets. We also find that foreign banks transmit to Main Street a larger portion of similar financial shocks than domestic banks. The observed decline in credit is greater among high-risk firms and firms with fewer tangible assets.
Keywords: E44; E51; F34; G21; 330; bank lending channel; business lending; credit crunch; financial crisis; Internationale Bank; Kreditrationierung; Kreditgeschäft; Finanzkrise; Unternehmensfinanzierung; KMU; Osteuropa